Smart approaches to waste management for post‐COVID‐19 smart cities in Japan. Issue 2 (30th June 2020) - Onoda, Hiroshi
Abstract : The COVID‐19 crisis has had a great impact on Japanese society. The author is rapidly going online and trying to make the transition to a new way of life. This study discusses the topics before and after the COVID‐19 pandemic in Japan. Then, smart approaches to waste management for post‐COVID‐19 smart cities in Japan are described by illustrating the results of the author's research group. Specifically, the author states that virtual reality can be an effective solution for remote education. The work chain management system contributes to the promotion of cashless in addition to the traceability of waste. The multi‐benefits mobility system that supports self‐driving will contribute to the automatic garbage collection by linking it to smart garbage bins. Besides, remote control of waste incineration facilities and robotic arms in waste treatment and recycling facilities will take on more importance. The author believes that the COVID‐19 crisis could be an opportunity to accelerate smart city initiatives in Japan.